ڕەنگدانەوەی نامۆیی لە ڕۆمانی (مۆزەخانەی کوڕە قژدرێژ)ی کاروان عومەر کاکەسووردا - عیسا, سه‌رپه‌رشتیار: پ.ی.د. هاوژین صلیوه‌; نوری, خوێندکاری دکتۆرا: م.ی. شوان عثمان (Sulaimani Journal for Humanities, 2023)
Alienation is a phenomenon that every human may be involved according to the age and circumstance that he or she lives in. If we search the literature of nations, we see that alienation has reflected and occupied a wide space in their literary products, the authors and poets have expressed and mentioned this phenomenon in their works. And from stage to stage this term has been changed according to circumstance, time and appeared as a complicated, multidimensional term. In the novels of (Karwan Kakaswr) as a prominent kurdish novelist, this phenomenon can be obviously felt. In the novel of (Museum of long hair boy), each one of (self- social - geographical) alienation has been reflected. The main character in the novel, is an alienated one to the society traditions and considers them as a fake past, that's why he rebels and wants to break them, he enjoys facing his society and doesn't pay attention of the obstructions. The characteristic of the novelist is that he has become an alienated passage and this alienation is in his existence and has reflected in his language.
Keywords: Museum of long hair boy; Alienated person; Social alienation; Selfalienation; Geographical alienation; Underground woman; Salon woman